HPA-Axis and Inflammatory Reactivity to Acute Stress is Related with Basal HPA-Axis Activity - Chen, Xuejie (Psychoneuroendocrinology, 2017)
INTRODUCTION: Inflammation is drawing attention as pathway between psychosocial stress and health, and basal HPA axis activity has been suggested to exert a consistent regulatory influence on peripheral inflammation. Here we studied the relationship between basal HPA axis activity and inflammatory and HPA axis acute stress reactivity. METHODS: We recruited 48 healthy individuals and collected saliva for diurnal cortisol sampling at 6 points. Participants were previously exposed to the Trier Social Stress Test (TSST) on two consecutive days. Plasma interleukin-6 (IL-6) and salivary cortisol reactivity to acute stress were measured, and their relationships with basal activity were analyzed. RESULTS: Steeper cortisol awakening response (CAR) linear increase was related with stronger cortisol stress reactivity (γ=0.015; p=0.042) and marginally significantly with greater habituation (γ=0.01; p=0.066). Greater curvilinearity of CAR was related with stronger cortisol reactivity (γ=−0.014; p=0.021) and greater cortisol habituation (γ=−0.011; p=0.006). Steeper daily linear decline was related with significant or marginally significantly stronger cortisol and IL-6 reactivity (cortisol: γ=−0.0004; p=0.06; IL-6: γ=−0.028; p=0.031) and greater habituation (cortisol: γ=−0.002; p=0.009, IL-6: γ=−0.015; p=0.033). Greater curvilinearity of daily decline was related with stronger IL-6 reactivity (γ=0.002; p=0.024) and also greater cortisol and IL-6 habituation (cortisol: γ=0.00009; p=0.03, IL-6: γ=0.001; p=0.024). CONCLUSIONS: Patterns of basal HPA axis activity that are related with healthier outcomes were found to be related with stronger initial cortisol and IL-6 reactivity and greater habituation. This is an important step in understanding the long-term health implications of acute stress responsiveness, and future studies should employ longitudinal designs to identify the direction of these relationships.